Turkish thoracic society early career members task force group's virtual congress notes: european respiratory society international congress 2020 - ARIKAN, HÜSEYİN (My University, 2022)
In this article, Early Career Task Force Group members of the Turkish Thoracic Society summarize the European Respiratory Society 2020 virtual congress. Current developments in the field of respiratory diseases were compiled with the addition of sessions specific to coronavirus disease 2019 this year. Almost all of the congress sessions were examined, and the important and striking results of the congress were highlighted. Congress sessions were attended by expert researchers, and the prominent messages of each session were highlighted in short summaries. They were then grouped under relevant titles and ranked in order of meaning and relation. It was finalized by a team of researchers.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Respiratory diseases; Lung health; European Respiratory Society; congress highlights; PULMONARY ARTERIAL-HYPERTENSION; EARLY-LIFE ORIGINS; CELL LUNG-CANCER; CYSTIC-FIBROSIS; HEPATIC STEATOSIS; PARENTAL SMOKING; OPEN-LABEL; DOSE CT; SLEEP; MANAGEMENT